The redundancy effect under morphogenetic and environmental fluctuations. The case of the Dianthus pungens group. (2nd January 2022) - Castro, Isaura; Rocha, João; Martins, Maria; Carnide, Valdemar; Martín, Juan Pedro; Veiga, Pedro; Serafim, Ana Beatriz; Amich, Francisco; Ramírez-Rodríguez, Rubén; Colombo, Giacomo; Crespí, António Luis
Abstract: This study describes the morpho-environmental fluctuations, and the haplotypic variability of a taxonomic group, in order to understand the phenotypic capacity to respond to environmental variations. The Dianthus pungens group was selected as the taxonomic cluster for the purpose of this study. One species and five subspecies occur along the western Mediterranean basin, between SE France and NW Morocco. One clustering of morphological (223 locations) and environmental (350 locations) combinations was correlated with the haplotypic results obtained from 28 locations and 89 individuals. Morpho-environmental fluctuations were described, as well a highly redundant morphological response in the studied area. Similar results were observed for haplotypic combinations. Redundancy effect is described as a consequence of its recent origin and the intense glacial and interglacial changes across the Plio-Pleistocene period. The observed environmental variability was not significantly correlated with morphogenetic divergences. Based on the observed patterns of morpho-environmental variations no specific or subspecific combinations are recommended. However, D. hispanicus (eastern Iberian Peninsula) showed possible morpho-environmental divergences with D. brachyanthus - D. gredensis - D. langeanus (mountain systems of the western and central Iberian Peninsula, Pyrenees, and Sierra Nevada -SE Spain-).